2020
DOI: 10.1186/s11671-020-3287-1
|View full text |Cite|
|
Sign up to set email alerts
|

Tin and Oxygen-Vacancy Co-doping into Hematite Photoanode for Improved Photoelectrochemical Performances

Abstract: Hematite (α-Fe 2 O 3 ) material is regarded as a promising candidate for solar-driven water splitting because of the low cost, chemical stability, and appropriate bandgap; however, the corresponding system performances are limited by the poor electrical conductivity, short diffusion length of minority carrier, and sluggish oxygen evolution reaction. Here, we introduce the in situ Sn doping into the nanoworm-like α-Fe 2 O 3 film with ultrasonic spray pyrolysis method. We show that the current density at 1.23 V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
5
17
0
Order By: Relevance
“…It is reported that heteroatoms doping is very similar to the regulation of adsorbed oxygen content in oxides. [37,38] So the ratio of lattice oxygen to adsorbed oxygen of SnS 2 /NiO decreases to 1.56. In addition, the O 1s spectra of SnS 2 /NiO with different NiO contents are shown in Figure S4.…”
Section: Resultsmentioning
confidence: 98%
“…It is reported that heteroatoms doping is very similar to the regulation of adsorbed oxygen content in oxides. [37,38] So the ratio of lattice oxygen to adsorbed oxygen of SnS 2 /NiO decreases to 1.56. In addition, the O 1s spectra of SnS 2 /NiO with different NiO contents are shown in Figure S4.…”
Section: Resultsmentioning
confidence: 98%
“…It is generally accepted that the OVs in hematite serve as electron donors, resulting in improved electrical conductivity. [6][7][8][9]56 The donor density (N d ) of the samples was estimated using Mott− Schottky analysis. Figure 5a In an electrochemical cell, the bulk capacitance (C bulk ) of an electrode is related to the applied potential (V) by the Mott− Schottky equation as follows…”
Section: Resultsmentioning
confidence: 99%
“…The ability of hematite to achieve a high water oxidation performance, however, has been hindered by its low electrical conductivity (10 –14 Ω –1 cm –1 ), extremely short photoexcited carrier lifetime, and tiny minority carrier diffusion length . The introduction of oxygen vacancy (OV) in a nanostructured hematite thin film has been regarded as an effective method which enhances its PEC performance. OV is a type of defect that may be present in metal oxides . Two electrons are left by each missing oxygen atom in the hematite lattice .…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it came to the authors’ attention that an incomplete version of affiliation 1 had been provided; ‘Soochow University’ was missing from the affiliation.…”
Section: Correction To: Nanoscale Research Letters (2020) 15:54 10118...mentioning
confidence: 99%